2011
DOI: 10.1126/scisignal.2001430
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Potency and Maximal Efficacy Reveal a Mechanism of Efficient T Cell Activation

Abstract: T cell activation, a critical event in adaptive immune responses, follows productive interactions between T cell receptors (TCRs) and antigens, in the form of peptide-bound major histocompatibility complexes (pMHCs) on the surfaces of antigen-presenting-cells. Upon activation, T cells can lyse infected cells, secrete cytokines, such as interferon-γ (IFN-γ), and perform other effector functions with various efficiencies that directly depend on the binding parameters of the TCR-pMHC complex. The mechanism that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 44 publications
5
81
0
Order By: Relevance
“…First, the dose-response seemed to exhibit a bell shape with reduced cytokine production at high pMHC concentrations. This bell shape was less pronounced or absent for low-affinity ligands, which is consistent with published studies reporting a sigmoidal dose-response for low-affinity ligands (14,15,17,18,21,23,41). Second, the peak amplitude of the bell-shaped dose-response was similar for pMHCs despite large differences in their affinities.…”
Section: T-cell Activation In Response To a 1 Million-fold Variation supporting
confidence: 80%
See 1 more Smart Citation
“…First, the dose-response seemed to exhibit a bell shape with reduced cytokine production at high pMHC concentrations. This bell shape was less pronounced or absent for low-affinity ligands, which is consistent with published studies reporting a sigmoidal dose-response for low-affinity ligands (14,15,17,18,21,23,41). Second, the peak amplitude of the bell-shaped dose-response was similar for pMHCs despite large differences in their affinities.…”
Section: T-cell Activation In Response To a 1 Million-fold Variation supporting
confidence: 80%
“…Studies performed over the last two decades have focused on empirically mapping the relationship between pMHC affinity and T-cell activation (5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A number of studies have reported an optimal pMHC affinity for T-cell activation, but other studies have failed to observe the optimum.…”
mentioning
confidence: 99%
“…5). Our observations are corroborated by mathematical modeling (42,43) demonstrating that, in accordance with the productive hit rate model, as the density of cognate pMHC increases on the surface of an APC, serial triggering becomes less of a determinant of T cell activation for TCR having longer dwell-times. Further, no amount of cognate pMHC can compensate for the reduced T cell responses in the case of TCR having larger k off values (short half-life).…”
Section: Discussionsupporting
confidence: 75%
“…The stability of TCR binding for the peptide-MHC complex is a key determinant for T-cell activation. Several lines of evidence argue for a close relationship between cell surface dissociation kinetics (k off ) and functional T-cell responses (5,(23)(24)(25)(26)). Yet, rapid and accurate screening methods to measure TCR-pMHC binding kinetics are still needed to isolate antigen-specific T cells expressing TCRs of high binding avidity.…”
Section: Discussionmentioning
confidence: 99%